The Relationship Between Health Service Support at Community Health Centers and Family Caregiver Coping for Patients with Type 2 Diabetes Mellitus - Setyoadi; Annisa wuri Kartika; Nunik Nurani; Yati Srihayati; Niko Dima Kristianingrum; Dina Dewi Sartika Lestari Ismail; Haliza Hasan; Mohd Khairul Zul Hasymi Bin Firdaus (Window of Health : Jurnal Kesehatan, 2024)
Type 2 Diabetes Mellitus (T2DM) is a chronic disease that requires long-term treatment and often necessitates the assistance of family caregivers. One of the challenges faced by family caregivers in caring for T2DM patients is the psychological pressure that can affect their ability to cope with the situation. Psychological stress demands external support, particularly from Community Health Center (Puskesmas) services, which becomes crucial. This study aims to explore the relationship between Community Health Center support services and the coping mechanisms of family caregivers for T2DM patients in Malang, Indonesia. This research employs an observational design with a cross-sectional approach involving 324 family caregivers selected through cluster random sampling technique from an average of 1,787 monthly visits, using the Lamesow sample size formula from 1997. Data collection was conducted using the Health Service Support Questionnaire (HSSQ) and the Family Coping Index (FCI). Data analysis utilized the Spearman Rank test. The data analysis indicated a p-value (0.000) < α (0.05), which shows a significant relationship between health service support (Puskesmas) and the coping mechanisms of family caregivers. In conclusion, there is an important relationship between primary health service support and the coping strategies of families caring for T2DM patients. The findings of this study recommend the implementation of special programs for family caregivers of T2DM patients, aiming to improve the skills and effectiveness of home care assistance.